INFLUENCE OF MANAGERIAL PERFORMANCE: WORK MOTIVATION, LEADERSHIP STYLE AND WORK EXPERIENCE (LITERATURE REVIEW STUDY) - Setyo Widodo, Djoko (Dinasti International Journal of Digital Business Management, 2021)
Literature article Reviewing the Effect of Work Motivation, Leadership Style and Work Experience on Managerial Performance is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Work Motivation has an effect on Managerial Performance; 2) Leadership Style has an effect on Managerial Performance; and 3) Work Experience has an effect on Managerial Performance. Apart from these 3 exogenous variables that affect the endogenous variable of Managerial Performance, there are still many other factors including Education, Commitment, and Communication variables.